2017
DOI: 10.1002/rmb2.12045
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal undernutrition disrupted the sexual maturation, but not the sexual behavior, in male rats

Abstract: PurposeExposure to various stressors, including psychological, metabolic, and immune, in the perinatal period induces long‐lasting effects in physiological function and increase the risk of metabolic disorders in later life. In the present study, sexual maturation and sexual behavior were assessed in prenatally undernourished mature male rats.MethodsAll the pregnant rats were divided into the maternal normal nutrition (mNN) group and the maternal undernutrition (mUN) group. The mUN mothers received 50% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…In addition, the cognitive and reading abilities of the children of undernourished mothers were also lower than those of the children of normally nourished mothers . Furthermore, in rats we have shown that sexual maturation was disturbed in both the male and female offspring of undernourished mothers . These findings indicate that prenatal nutritional stress has adverse effects on physiological, psychological, and reproductive functions, and these changes might cause certain diseases in later life.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, the cognitive and reading abilities of the children of undernourished mothers were also lower than those of the children of normally nourished mothers . Furthermore, in rats we have shown that sexual maturation was disturbed in both the male and female offspring of undernourished mothers . These findings indicate that prenatal nutritional stress has adverse effects on physiological, psychological, and reproductive functions, and these changes might cause certain diseases in later life.…”
Section: Introductionmentioning
confidence: 75%
“…Newly purchased male and female rats (9 weeks of age) were used as partners for the sexual behavior test. In the sexual behavior test, a pair of rats was put in a cage together after the male had been allowed 5 minutes' habituation in the cage, and sexual behavior was monitored via a video recording for 30 minutes . Mounting (the male places its forequarters on the hindquarters of the female from behind), intromission (mounting with vaginal insertion), and ejaculation (mounting with vaginal insertion and emission) were evaluated as male sexual behaviors, and proceptive behavior (hopping and darting, ear wiggling) and receptive behavior (the lordosis quotient [LQ]: lordotic responses/mounts × 100, and the lordosis rating [LR]: the mean number of lordosis reflexes in the first 10 mounts) were evaluated as female sexual behaviors .…”
Section: Methodsmentioning
confidence: 99%
“…From PND35, the pups were inspected daily for preputial separation (PS), which is an indicator of male puberty. The penis was evaluated by examining and attempting to retract the prepuce to determine if it had separated from the glans penis (Stoker et al, 2000; Matsuzaki et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks later, estradiol benzoate (10 μg/body) dissolved in 0.1 mL sesame oil was injected subcutaneously (s.c.) into the backs of the female rats at 48 h and 24 h before the test session. Progesterone (1 mg/body) dissolved in 0.2 mL sesame oil was injected s.c. into the female rats 4 h before the test session (Govic et al, 2008; matsuzaki et al, 2017). At 11 and 12 weeks of age, sexual behavior tests were conducted under the following conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation